Innovative Therapeutic and Delivery Approaches Using Nanotechnology to Correct Splicing Defects Underlying Disease - Suñé-Pou, Marc; Limeres, María J.; Moreno-Castro, Cristina; Hernández-Munain, Cristina; Suñé-Negre, Josep M.; Cuestas, María L.; Suñé, Carlos (Frontiers in Genetics, 2020)
Alternative splicing of pre-mRNA contributes strongly to the diversity of cell- and tissue-specific protein expression patterns. Global transcriptome analyses have suggested that >90% of human multiexon genes are alternatively spliced. Alterations in the splicing process cause missplicing events that lead to genetic diseases and pathologies, including various neurological disorders, cancers, and muscular dystrophies. In recent decades, research has helped to elucidate the mechanisms regulating alternative splicing and, in some cases, to reveal how dysregulation of these mechanisms leads to disease. The resulting knowledge has enabled the design of novel therapeutic strategies for correction of splicing-derived pathologies. In this review, we focus primarily on therapeutic approaches targeting splicing, and we highlight nanotechnology-based gene delivery applications that address the challenges and barriers facing nucleic acid-based therapeutics.